Gender and age make no difference in the re-irradiation of painful bone metastases: A secondary analysis of the NCIC CTG SC.20 randomized trial. Issue 3 (March 2018) - Chow, Ronald; Ding, Keyue; Ganesh, Vithusha; Meyer, Ralph M.; van der Linden, Yvette M.; Roos, Daniel; Hartsell, William F.; Hoskin, Peter; Wu, Jackson S.Y.; Nabid, Abdenour; van Acht, Manouk; Wanders, Rinus; et al.
Abstract: Background and purpose: Patient's gender and age may influence physicians in prescribing palliative radiotherapy. The purpose of this secondary analysis of the National Cancer Institute of Canada Clinical Trials Group Symptom Control Trial SC.20 was to explore the gender and age differences in pain and patient reported outcomes in cancer patients with bone metastases undergoing re-irradiation. Materials and methods: Response to radiation was evaluated using the International Bone Metastases Consensus Endpoint Definitions. Patients completed the Brief Pain Inventory (BPI) and European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (C30) before and 2 months after re-irradiation. Results: A total of 847 patients were analyzed. At baseline, men had more dyspnea, and mild pain. Older patients consumed less analgesic. More women reported clinically significant improvement in mood and enjoyment of life in the BPI after radiation. Similarly, younger patients reported better improvement in enjoyment of life. There were no significant gender or age differences in overall survival, response to radiation, or in C30 scores at 2 months. Conclusion: Similar benefit in terms of pain relief was observed across all patient groups. Cancer patients with bone metastases should be offered palliative re-irradiation irrespective of gender or age. Trial Registration: NCT00080912; https://clinicaltrials.gov/ct2/show/NCT00080912.